Pelatihan Dasar Motor-Motor Listrik kepada Siswa-Siswi SMA Fransiskus Bandar Lampung - Charles Ronald Harahap; Misfa Susanto; Yetti Yuniati (FT Universitas Lampung, 2026)
Electric motors are used to drive various electrical loads such as fans, washing machines, refrigerators, and other devices. The electric motor used in this study is a direct current motor, which is widely applied in industry, household appliances, and transportation systems. A DC motor is an electric motor that utilizes direct current as its energy source. A DC motor consists of two main parts, namely the stator and the rotor, where each part is wound with coils to generate a magnetic field when supplied with direct current. SMA Fransiskus offers physics courses that cover magnetism and further develop the study of magnetic physics through the application of DC motors. Therefore, this community service activity aimed to provide knowledge and training on the application of magnetic physics in DC motors through a basic DC motor construction workshop. The method employed consisted of educational outreach by providing knowledge about the fundamentals of DC motors and their construction procedures. This was followed by training, mentoring, and demonstrations on the basic construction of DC motors, during which the students of SMA Fransiskus actively participated in building simple DC motors. After the training sessions, an evaluation of the community service activities was conducted. The entire community service program was successfully implemented, and the students of SMA Fransiskus showed great interest and enthusiasm for the training because it enabled them to gain hands-on experience in constructing basic DC motors as an application of magnetic physics learned in their coursework. As a result, the students of SMA Fransiskus improved their understanding and knowledge of the application of magnetic physics through the basic DC motor construction training.